Ipteks bagi Masyarakat Kelompok Produsen Dadih di Daerah Tilatang Kamang Kabupaten Agam - Amna Suresti; Salam Ningsih Aritonang; Rahmi Wati (Warta Pengabdian Andalas, 2017)
In West Sumatra, buffalo milked to produce milk that is processed into curd. The curd was traditional food made from buffalo milk that is cured at room temperature for 2 to 3 days in a bamboo tube closed banana leaves, creamy white with a dense and smooth texture, flavor and aroma typical acid (smell bamboo). Targets was increase efforts to reproduce the variation of production and product (product diversification: Ice curd, buttermilk pudding, curd Aroma Tape, Jelly Candy curd) by using a particular technology, and improving packaging curd in order to expand the market that leads to an increase in income of farmers and businessman curd). Based on the report of activities that have been described, here are some conclusions that can be produced (1). Entrepreneurial motivation training activities can increase entrepreneurial spirit curd producers in an effort to support the development activities of the business group. (2) The maintenance management counseling buffaloes able to develop the knowledge of farmers in raising livestock buffalo. (3). Pilot training and diversification curd able to increase revenue. (4). Promotion and development of network marketing has been used as a marketing strategy to increase production volume group.